If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying e + 6 = 3e + -12 Reorder the terms: 6 + e = 3e + -12 Reorder the terms: 6 + e = -12 + 3e Solving 6 + e = -12 + 3e Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-3e' to each side of the equation. 6 + e + -3e = -12 + 3e + -3e Combine like terms: e + -3e = -2e 6 + -2e = -12 + 3e + -3e Combine like terms: 3e + -3e = 0 6 + -2e = -12 + 0 6 + -2e = -12 Add '-6' to each side of the equation. 6 + -6 + -2e = -12 + -6 Combine like terms: 6 + -6 = 0 0 + -2e = -12 + -6 -2e = -12 + -6 Combine like terms: -12 + -6 = -18 -2e = -18 Divide each side by '-2'. e = 9 Simplifying e = 9
| y=2n^2+2n-24 | | (16000-x)^(3/2) | | 5(x-6)+4=2(x-7) | | -16x^2+48+6=0 | | 10m-1/4m10m-1/4m- | | 5m+12=7 | | 5y-30x=40 | | x*.55=3000 | | y^2=16+4x+2 | | y+10-2y-1=180 | | k-76.98=-3.56 | | -R+8.5=14.2 | | k-76.98=3.56 | | h(t)=-16t+60t | | x-8.7=-3.5 | | 34-[4-9]-15= | | 7-8x-2=-48+3x-13 | | 15-[-7*4]= | | 6.3x+3=5.3x | | 6x=690 | | (1-3x)(2x-3)(2x-3)=0 | | -18[2-7]= | | 8*3+3y=24 | | 138-x=138-690 | | 22+[-7]-20= | | 777777777777777777777777777777777n=7777777+5 | | 3k-8=-32 | | x+2x+3x=846 | | 9p^2+48p+48=0 | | 846=x+2x+3x | | -4(-28)+7y=-28 | | y=ln(ln(3x)) |